Pendidikan Kewargaan untuk Demokrasi di Indonesia - Azyumardi Azra (Unisia, 2005)
"All societies have a continuing interest in the way their young people are prepared for citizenship and learn to take part in public affairs. [Since] the 1990s, this has become a matter of increased importance not only in societies striving to establish or re-estab lish democratic govemments, but also in societies with continous and long-established democratic traditions. What effective citizenship means and the role of format education in building a civic culture is important not only to govemments and policy-makers, but also to the public at large" (Torney-Purta, Schwille &Amedeo, 1999:12). 'There is an old saying that the course of civilization is a race between catastrophe and education.  In a democracy such as ours, we must make sure that education wins the race" (John F. Kennedy, 1958, daiam Print et all, 1999:9).